Limitation of the General Assembly’s Authority to Dismiss the Members of the Board of Directors - Veliye Yanlı; Cem Veziroğlu (İstanbul Hukuk Mecmuası)
Provisions that restrict the dismissal of board members can serve to protect the interests of a company’s legal personality, minority shareholders, and board members in various contexts. It also enables control to be shared between majority and minority shareholders in legal systems where the block shareholding structure is the prevailing model, such as in Türkiye. However, these types of provisions limit the absolute and inalienable power of the general assembly to dismiss members from the board of directors. Thus, in cases where the trust has been broken between a board member and the company, these provisions limit the ability to dismiss the relevant member from duty. Nevertheless, an uncertainty exists within Turkish Law regarding whether the arrangements limiting the dismissal of board members are valid within the corporate structure. This study seeks answers to the following two questions about the possibility of limiting the general assembly’s authority to dismiss board members through a regulation in the articles of association: Can such a decision be tied to a certain period or to the presence of justified reasons or of certain conditions, and can special quorums be called for in a general assembly meeting regarding such a decision. While the answer to the first question in the existing doctrine is generally negative, the answer to the second question is positive. In accordance with the opinion adopted in this study, limiting the dismissal of members of the board of directors should not be possible through regulations such as just cause, conditions, time, or sanctions. Similarly, increasing the meeting and/or decision quorums should also not be possible regarding the dismissal of members from a board of directors.